2003
DOI: 10.2176/nmc.43.477
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Surgery for the Treatment of Spontaneous Dural Carotid-Cavernous Fistulas

Abstract: Endovascular treatment for a spontaneous dural carotid-cavernous fistula (CCF) is an established treatment, but stereotactic radiosurgery might provide a less-invasive alternative in selected cases. Four women aged 67 to 79 years (mean 72.0 years) with spontaneous dural CCFs presented with chemosis or bruit. Angiography revealed arteriovenous fistulas in the cavernous portion. Three cases were Barrow type D and one was type B converted from type D. Stereotactic gamma knife surgery was performed with a marginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 10 publications
2
12
0
1
Order By: Relevance
“…Other small series of patients with indirect CCFs have shown long-term obliteration of the fistula after treatment with radiosurgery in 75%-100% of patients. 3,17,28,53,64 Radiosurgery should not be used in emergency cases, as there is a latency of several months to years before complete obliteration of the CCF is accomplished. …”
Section: Radiosurgical Interventionmentioning
confidence: 99%
“…Other small series of patients with indirect CCFs have shown long-term obliteration of the fistula after treatment with radiosurgery in 75%-100% of patients. 3,17,28,53,64 Radiosurgery should not be used in emergency cases, as there is a latency of several months to years before complete obliteration of the CCF is accomplished. …”
Section: Radiosurgical Interventionmentioning
confidence: 99%
“…20 This may be a result of their proclivity to be small and low-flow. Although this would appear to make patients with DAVFs ideal candidates for radiosurgery, those with CVD have a much more malignant natural history and require expedient curative treatment via surgical or endovascular means.…”
Section: Discussionmentioning
confidence: 99%
“…Across our review, the study with the highest mean treatment volume (9.6 cm 3 ) demonstrated the lowest overall obliteration rate (41%). 9 On the other hand, the study of Onizuka et al 20 reported a 100% obliteration rate for 4 cavernous DAVFs with treatment volumes ranging from 0.8 to 1.8 cm 3 . Thus, in addition to cavernous location and lack of CVD, small DAVF size likely improves obliteration rates after SRS.…”
mentioning
confidence: 98%
“…[5][6][7][8][9][10] In AVM/DAVF radiosurgery, irradiation is delivered in a single fraction stereotactically to only the nidus of an AVM or fistula of a DAVF. Our current clinical practice of AVM/DAVF radiosurgery, integrated stereotactic imaging (MR imaging/MRA and x-ray digital subtraction angiography) is used for nidus/fistula delineation.…”
mentioning
confidence: 99%